Islamic Civilization and the Development of the Saluan Tribe in Mondonun - Tune, Moh Wirasto (Green Publisher Indonesia, 2023)
This study aims to understand Islamic civilization and the development of the Saluan tribe in Mondonun qualitatively. The method used is a literature study on the history and development of Islam and the Saluan tribe in Mondonun. The results of the study show that Islamic civilization has played an important role in the development of the Saluan tribe in Mondonun. Islam entered Mondonun in the 17th century through trade and marriage between Arabs and Malays. Islam brings changes in the mindset and culture of the Mondonun people, including in terms of religion, education, and social matters. The development of the Saluan tribe in Mondonun was also influenced by economic and political factors. They were an ethnic group who traded with Arabs and Malays, and later became part of the Muslim Mondonun community. The development of the Saluan tribe was also influenced by relations with the Dutch and Indonesian colonial governments. This study concludes that Islamic civilization and the development of the Saluan tribe in Mondonun are interrelated and have a significant influence on one another. This study can be the basis for further research on the history and development of Islam and the Saluan tribe in Mondonun, as well as for further understanding of Islamic civilization in other regions of Indonesia.